2022
DOI: 10.1038/s41598-022-05702-0
|View full text |Cite
|
Sign up to set email alerts
|

In situ vaccination using unique TLR9 ligand K3-SPG induces long-lasting systemic immune response and synergizes with systemic and local immunotherapy

Abstract: Although checkpoint inhibitors (CPIs) have changed the paradigm of cancer therapy, low response rates and serious systemic adverse events remain challenging. In situ vaccine (ISV), intratumoral injection of immunomodulators that stimulate innate immunity at the tumor site, allows for the development of vaccines in patients themselves. K3-SPG, a second-generation nanoparticulate Toll-like receptor 9 (TLR9) ligand consisting of K-type CpG oligodeoxynucleotide (ODN) wrapped with SPG (schizophyllan), integrates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…A therapeutic effect of CpG stimulation on mesothelioma growth has been reported previously in a model of mesothelioma using orthotopic xenografts in immunodeficient mice (28). CpG stimulation has also therapeutic effect on pancreas adenocarcinoma and colorectal cancer models (29). TLR9 agonists have been tested in early human clinical trials, including in combined therapies (30).…”
Section: Discussionmentioning
confidence: 77%
“…A therapeutic effect of CpG stimulation on mesothelioma growth has been reported previously in a model of mesothelioma using orthotopic xenografts in immunodeficient mice (28). CpG stimulation has also therapeutic effect on pancreas adenocarcinoma and colorectal cancer models (29). TLR9 agonists have been tested in early human clinical trials, including in combined therapies (30).…”
Section: Discussionmentioning
confidence: 77%
“…Lindsay et al coloaded the hydrophobic chemotherapeutic drug doxorubicin (DTX) and Incorporation of cholesterol-modified TLR9 agonist in synthetic high-density lipoprotein cholesterol (HDL) nanodiscs, and found that the use of DTX-sHDL/CpG inhibited tumor growth and prolonged animal life. 312,313 These findings showed that TLR9 mediates gastric cancer inflammation, is abundantly expressed in GC samples, and facilitates the migration of cancer cells. 314,315 In addition, the TLR9 rs5743836 and rs187084 polymorphisms were linked to a significant oncogenic risk of gastric cancer.…”
Section: Tlr9mentioning
confidence: 90%
“…Even so, their mechanisms of action must be elucidated for maximum therapeutic benefit 304,305,308 . Moreover, researchers have shown that TLR9 agonists are also highly effective and beneficial when combined with traditional cancer treatment (i.e., radiotherapy or chemotherapy) 312,313 …”
Section: Tlr‐related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ vaccination is an alternative route of administration in addition to standard subcutaneous and intravenous injections for the early diagnosis and treatment of CRC, which relies on endoscopy-guided puncture. In situ injection of K3-SPG as a monotherapy can fully induce systemic and persistent memory responses, and the combination of systemic administration of check point inhibitors (CPIs) and local administration of CD40 agonists has a synergistic antitumor effect ( 83 ).…”
Section: Adjuvants and Administration Routes Of Colorectal Cancer Vac...mentioning
confidence: 99%